Combating land degradation and desertification and enhancing food security: towards integrated solutions - Stringer, Lindsay C. (2012)
This paper seeks to provide an overview of the relationships between food insecurity, land degradation and desertification, and its antithesis, food security and sustainable land management. It places particular focus on the worlds drylands (i.e. arid, semi-arid and dry sub-humid areas), but situates the review within the wider context of global food systems and the macro-processes that drive land degradation and desertification. It is revealed that food insecurity can be attributed to a range of demand-side and supply-side causes, which include political, economic, social and environmental factors. Land degradation and desertification are shown to be exogenous issues that can amplify and aggravate food insecurity. Addressing desertification, including land, soil, water and plant degradation, can facilitate or ease the food security dilemma, but may not completely solve it in the presence of other underlying causes.